MODERNIZING THE SYSTEM OF PREPARING PHYSICAL EDUCATION SPECIALISTS FOR PROFESSIONAL AND CAREER ACTIVITIES BASED ON MODERN APPROACHES - Xolboeva Gulxayo Xolboyevna (Research Focus International Scientific Journal, 2025)
This article highlights the importance of introducing a system that supports long-term professional training and fosters career advancement for highly qualified specialists in the field of sports, especially in the context of current social instability. The continuous growth of athletic achievements increases the demand for professionals with modern thinking and advanced competencies. Enhancing specialists’ professional success in line with current requirements has become a pressing task, calling for a new stage of development in the sphere of physical education. In developed countries, the creation of a nationally integrated and modernized model for training personnel in physical education is considered a key priority.